ENT300 Fundamental of Entrepreneuship Business Plan : Al-Khalilah Hijab / Siti Helida Binti Hasbi... [et.al] - Hasbi, Siti Helida; Julis, Amiratulmasnisah; Wan Ibrahim, Sharifah Lydia Haziyah; Husni, Nurshyaneeza; Nordin, Ummu Khalilah (2014)
Al-Khalillah Hijab is new company that operated in Malaysia. It is the first company that being managed by bumiputera. The name of this company is come out from our friends last name Khalilah. It shows that how we positioning our product in costumers minds until they can remember our unique and classic company name.